New narratives for old : the historical method of reading early Christian theology : essays in honor of Michel René Barnes - Barnes, Michel R.; Briggman, Anthony; Scully, Ellen (CUA studies in early Christianity., 2022)
"This volume both defines and illustrates the methodology of historical theology, especially as it relates to the study of early Christianity, and situates historical theology among other methodological approaches to early Christianity, including confessional apologetics, constructive theology, and socio-cultural history. The volume begins with an introductory essay that orients readers to various approaches to early Christian literature, it moves to two technical essays that define the historical method of studying early Christian theology, and then it illustrates the practice of this method with more than twenty essays that cover a period stretching from the first century to the dawn of the seventh"--